Metabolic syndrome is independently associated with increased 20-year mortality in patients with stable coronary artery disease. Issue 1 (December 2016) - Younis, Arwa; Younis, Anan; Tzur, Boaz; Peled, Yael; Shlomo, Nir; Goldenberg, Ilan; Fisman, Enrique; Tenenbaum, Alexander; Klempfner, Robert
Abstract Background Data regarding long-term association of metabolic syndrome (MetS) with adverse outcomes are conflicting. We aim to determine the independent association of MetS (based on its different definitions) with 20 year all-cause mortality among patients with stable coronary artery disease (CAD). Methods Our study comprised 15, 524 patients who were enrolled in the Bezafibrate Infarction Prevention registry between February 1, 1990, and October 31, 1992, and subsequently followed-up for the long-term mortality through December 31, 2014. MetS was defined according to two definitions: The International Diabetes Federation (IDF); and the National Cholesterol Education Program–Third Adult Treatment Panel (NCEP). Results According to the IDF criteria 2122 (14%) patients had MetS, whereas according to the NCEP definition 7446 (48%) patients had MetS. Kaplan–Meier survival analysis showed that all-cause mortality was significantly higher among patients with MetS defined by both the IDF (67 vs. 61%; log rank-p < 0.001) as well as NCEP (67 vs. 54%; log rank-p < 0.001) criteria. Multivariate adjusted mortality risk was 17% greater [Hazard Ratio (HR) 1.17; 95% Confidence Interval (CI) 1.07–1.28] in patients with MetS according to IDF and 21% (HR 1.21; 95% CI 1.13–1.29) using the NCEP definition. Subgroup analysis demonstrated that long-term increased mortality risk associated with MetS was consistent among most clinical subgroups excepted patients with renal failure (p value for interaction < 0.05). Conclusions Metabolic syndrome is independently associated with an increased 20-year all-cause mortality risk among patients with stable CAD. This association was consistent when either the IDF or NCEP definitions were used. Trial registration retrospective registered